“Comparison of Active Release Technique and Post Isometric Relaxation in Patients with Piriformis Syndrome” - Attiq Ur Rehman, Lal Gul Khan, Maria Khalid, Usman Mumtaz, Huma Akhtar, Ayesha Gondal, Sadaf Waris (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the effects of active release technique and post isometric relaxation on pain intensity, hip internal rotation and functional disability in patients with piriformis syndrome. Methodology: A randomized clinical trial extending from September 2020 to January 2021 was conducted at Shifa International Hospital, Islamabad. Thirty patients were included in the study using purposive sampling and were randomized through sealed envelope method. All patients were evaluated using visual analogue scale, goniometer and lower extremity functional scale. A self-structured questionnaire was designed for data collection. Two sessions per week were given for three consecutive weeks and a follow up after one month. Data was taken at baseline, after three weeks and after one month follow up. Data was analyzed using SPSS-20. Results: 30 patients were treated with mean age of 41.30±4.99. 17 females and 13 males were treated. Group A (active release technique) and Group B (post isometric relaxation) showed significant improvement within groups (P<0.05) in all outcome measures (VAS, Goniometer and LEFS). Intra group analysis after one month follow up showed no statistically significant difference in VAS and Goniometer (P>0.05). However, active release technique was found to be more effective in improving functional disability than post isometric relaxation (P<0.05). Conclusion: Inter group analysis showed that ART and PIR are equally effective in improving pain, hip internal rotation and functional disability. Intra group analysis showed that ART compared to PIR is more effective in improving functional disability in piriformis syndrome.